Efficient energy storage performance of in situ grown Co3V2O8-RGO composite nanostructure for high performance asymmetric Co3V2O8-RGO//RGO supercapacitors and consequence of magnetic field induced enhanced capacity. (15th December 2021) - Devi, Pooja; Srivastava, Manish; Kim, Nam Hoon; Lee, Joong Hee; Mishra, Debabrata
Abstract: In this work, cobalt vanadate/reduced graphene oxide (Co3 V2 O8 /RGO) composite nanostructure has been synthesized via in-situ reduction of graphene oxide (GO) in the presence of cobalt chloride and sodium metavanadate through hydrothermal following post calcinations treatment. Characterizations through various techniques have been performed to probe the physicochemical properties of Co3 V2 O8 /RGO, RGO and Co3 V2 O8 nanostructures. Our Results show that because of the synergistic effect, Co3 V2 O8 /RGO composite nanostructure exhibits superior electrochemical properties as compared to bare RGO and Co3 V2 O8 . At a current density of 0.5 A/g the specific capacity has been recorded to be 118.82, ∼179, and ∼241.67 Cg -1 in case of Co3 V2 O8, RGO and Co3 V2 O8 /RGO nanostructures, respectively. Moreover, Co3 V2 O8 /RGO composite nanostructure (positive electrode) and RGO (negative electrode) have been employed to prepare the asymmetric supercapacitor, exhibited high specific capacity (127.62Cg -1 ), energy density (28.36 Whkg −1 ), and power density (400 Wkg -1 ) at a current density 0.5 A/g. This asymmetric supercapacitor shows excellent capacity retention (∼91.64%) and columbic efficiency (∼98.61%) measured at a current density of 5 A/g after 10, 000 charge/discharge cycles. More importantly, a dramatic increase ∼170% (344 Cg -1 ) and ∼67% (185 Cg -1 ) in the specific capacity have been recorded at a current density of 0.5 A/g and 1.0 A/g, respectively when asymmetric supercapacitor device is subjected to an external magnetic field of strength of 0.5 T. Additionally, under the applied magnetic field, capacity retention ∼97.75% and columbic efficiency ∼98.84% has been recorded at a current density of 5 A/g after 10, 000 cycles. Graphical abstract: Image 1 Highlights: Synthesis of Co3 V2 O8 /RGO composite nanostructure via a facile in-situ reduction. Co3 V2 O8 /RGO nanostructure exhibited specific capacity of ~242 Cg -1 at 0.5 Ag -1 . Co3 V2 O8 /RGO exhibits ~103% higher specific capacity compare to bare Co3 V2 O8 NPs. ASc exhibits energy density ~28.36 Whkg -1 and power density ~ 400 Wkg -1 at 0.5 Ag -1 . Capacity retention ~91.64 % and columbic efficiency ~98.61 % at 5 Ag -1 after 10, 000 cycles. Magnetic field induced ~170% enhanced capacity at 0.5 Ag-1.